ESP TEACHER EDUCATION MODEL IN INDONESIAN CONTEXT - Silvani Umar Ali (Universitas Khairun, 2015)
English for Specific Purpose (ESP) course has been taught over the years in many in Indonesia. However, the ESP teaching practice in nationalwide are confronting with several serious problems. One of the major problems lies on its teachers. This paper will attempt to first review the existing ESP schools in Indonesia, then will briefly explain certain theories underlying ESP. The next, the paper will analyze the existing and the practice of ESP schools in several countries and will finally propose ESP teacher education models